Factors affecting work pressure among primary school teachers during the covid-19 pandemic in Malaysia - Mohd Attamimi Farouk Maarof; Abu Yazid Abu Bakar; Ifdil Ifdil (RedWhite Press, 2022)
Work stress exists in various organizations whether government or private sector. The spread of the COVID-19 pandemic around the world starting December 2019 caused work stress due to the closure of schools due to the Movement Control Order (MCO). This study involved 8 primary school teachers with more than 10 years of experience at Sekolah Kebangsaan Cheras Jaya, Taman Cheras Jaya, Balakong, Selangor who were involved in the Teaching and Learning (TL/PdP) process face to face for the “Catch Up Plan” programme (no rotation with online Home Teaching and Learning HTL/ PdPr) involving pupils in years 1, 2 and 6 and the process of TLH/PdPr online (there is rotation with face-to-face TL/PdP) involving pupils in years 3, 4 and 5 from 10 January 2022 to 25 February 2022. This study uses a mixed-method design, combining both quantitative method (DASS-21 Screening Test) and qualitative method (interviews). The results of the study found that four teachers experienced depression, anxiety and stress in severe level due to two dominant factors of work stress which is workload and time constraints.